179k views
14 votes
Y’all give me dis answer to

Y’all give me dis answer to-example-1

1 Answer

2 votes

Answer:

The solution is: (1,-3)

Explanation:

Given equations are:

x-y=4 Eqn 1

4x+y = 1 Eqn 2

Substitution involves finding value of a variable from one equation and putting in other equation

From equation 1

x = y + 4

Putting in equation 2


4(y+4) + y = 1\\4y+16+y = 1\\5y = 1-16\\5y = -15\\(5y)/(5) = (-15)/(5)\\y = -3

Putting y = -3 in equation 1


x- (-3) = 4\\x + 3 = 4\\x = 4-3\\x = 1

Hence,

The solution is: (1,-3)

User Valera Kolupaev
by
4.9k points